2010
DOI: 10.1002/j.2161-1939.2010.tb00100.x
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and Stages of Child‐Centered Play Therapy for a Child With Highly Disruptive Behavior Driven by Self‐Concept Issues

Abstract: Descriptions in this case study of child-centered play therapy (CCPT) for a boy referredfor highly disruptive behavior include observations of his process through stages of CCPT, teacher and parent ratings on the Child Behavior Checklist (Achenbach & Rescorla, 2001), and explanations of how CCPT worked for him.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Over the course of the study, parents and teachers were able to report significant these declines, as shown by mean differences on the Externalizing Problems scale as well as the Rule-Breaking and Aggressive Behavior subscales. These results coincide with studies that demonstrated the strength of CCPT in managing externalizing problems (Bratton et al, 2013;Cochran et al, 2017;Garza & Bratton, 2006;Nordling & Guerney, 1999). The once-weekly CCPT structure for handling externalizing problem behaviors as found effective by Schumann (2010), Ray et al (2017) and Tsai (2018) was likewise seen in this study.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Over the course of the study, parents and teachers were able to report significant these declines, as shown by mean differences on the Externalizing Problems scale as well as the Rule-Breaking and Aggressive Behavior subscales. These results coincide with studies that demonstrated the strength of CCPT in managing externalizing problems (Bratton et al, 2013;Cochran et al, 2017;Garza & Bratton, 2006;Nordling & Guerney, 1999). The once-weekly CCPT structure for handling externalizing problem behaviors as found effective by Schumann (2010), Ray et al (2017) and Tsai (2018) was likewise seen in this study.…”
Section: Discussionsupporting
confidence: 89%
“…Significant decreases in externalizing and internalizing problem behaviors were also found when CCPT was administered in nine 40-min sessions on a weekly basis (Tsai, 2018). In high poverty schools, a nine-session CCPT frame yielded moderate to large effects for externalizing problems, total problems, attention problems, and learning-related self-efficacy (Cochran et al, 2017). Ray (2008) found that effects increase with the number of sessions with largest effect sizes at 11–18 sessions but with demonstrative beneficial effects at 3–7 sessions.…”
Section: Structure Of Ccpt Sessionsmentioning
confidence: 99%
“…With limit setting, a child presenting externalizing behavioral concerns experiences different approaches to expressing feelings and behaviors that result in decreases in the child's oppositional behaviors (Trice-Black et al, 2013). The effectiveness of CCPT with externalizing behaviors has also been reported by previous researchers (Bratton et al, 2013;Cochran et al, 2011;Cochran, Cochran, Fuss, & Nordling, 2010;Ray et al, 2009;Schumann, 2010).…”
Section: How Ccpt Play Therapy Work For Children Exhibiting Internalmentioning
confidence: 68%
“…As the structure coefficients and corresponding 81% of variance accounted for in group differences suggest, it can be reasonably predicted that children might become less aggressive, more self‐regulated, and more empathic through participation in CCPT as compared with receiving no services at all. This finding suggests that CCPT may decrease aggression, which in turn may improve children's healthy functioning and development over time related to behavioral symptomatology, academic achievement, interpersonal functioning, ability to form and maintain relationships, and overall sense of contentment (Cochran et al, ; Connor, ; Kingston & Prior, ; Risser, ).…”
Section: Discussionmentioning
confidence: 99%
“…Without early intervention, children exhibiting aggressive behaviors are at an increased risk for highly externalized and problematic behaviors across the life span (Foulkrod & Davenport, ; Frick & White, ; Gathright & Tyler, ). In addition, such problematic behaviors have been shown to contribute to ongoing social, emotional, and academic concerns that affect children's academic and personal success (Bratton et al, ; Cochran, Cochran, Fuss, & Nordling, ; Ray, Blanco, Sullivan, & Holliman, ). In the face of such behavioral and emotional challenges, caregivers may quickly begin to feel hopeless regarding effective treatment options for the children.…”
mentioning
confidence: 99%